Pemenuhan Nutrisi Dan Alternatif Penghasilan Melalui Produk Olahan Ikan Bagi Masyarakat Penangkap Ikan Kelurahan Oesapa Kecamatan Kelapa Lima Kota Kupang - Muntasir Muntasir; Pius Weraman; Mustakin Sahdan; Sri Prilmayanti A.; Nadra Aga Iryani (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2020)
The sea fish caught by fishermen which are abundant in the province of East Nusa Tenggara have become one of the endless marine products, especially for groups of marine workers to be managed and utilized to produce value of goods that are of great selling value so that they can provide added value in income and increase the economy of marine workers, especially groups. the main catchers are fishermen and their families. Every day fishermen sell their catch fish both traditionally and with the use of machines and technology to second consumers in large volumes and with various types of fish. occasionally, the marketed fish is completely sold out to a second consumer, as a result it has to be stored or preserved in other forms that can long time such as being made into salted fish or dried fish. Another method taken is processing the fish caught by sea workers into other products that can be sold and are durable in the form of product diversification. This partnership program is expected to be an alternative fulfillment of family nutrition, especially animal protein, which is attractive to housewives and fishing families. Also increasing the added value, knowledge, use and processing of animal protein sources which can increase the nutritional value, texture, processing and products as a form application of university for science and technology, resulting products can be a form of effort to increase the income of fishermen's families so that the community of marine workers can be helped in economic problems.